Design and Development of Small Chamber-Type Low-pressure Plasma Surface Treatment Equipment to Improve the Shear Bond Strength of Materials for Dental Prostheses - Moon, Byung-Kwon; Ko, Kyoung-Tag; Lee, Jong-Tak; Ji, Min-Kyung; Bang, Jun-Ho; Ryu, In-Ho (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study was to design a small chamber-type equipment by investigating the influence of dental prostheses treatment on the shear bond strength.Methods/Statistical analysis: The equipment was designed for the requirement of dental prostheses surface treatment. Two groups of zirconia disks were treated with low-pressure plasma (LP) by the prepared equipment (13.7 mA, 625V, 8.6W and minimum vacuum degree) and atmospheric plasma jet (AP), individually. In addition, untreated disks were regarded as the control. One-way ANOVA analysis was used to compare different surface treating groups.Findings: The output of power supply graph indicated the equipment was obtained the steady power(48kHz). On comparison, it existed a statistically significant different between the LP group and the control group (p
Keywords: low-pressure plasma; surface treatment; equipment; dental prostheses; Shear bond strength.